PENGARUH JOB SATISFACTION DAN JOB INSECURITY TERHADAP TURNOVER INTENTION MELALUI WORK ENGAGEMENT - Safrudin, Afif; Indrawati, Mei; Soenarmi, Soenarmi (STIE PENA, 2023)
The purpose of this research is to describe and analyze the effect of job satisfaction and job insecurity on turnover intention through work engagement. This research is a quantitative research. The population in this study were employees of the Al-Fatimah Bojonegoro Modern Islamic Boarding School with a total of 120 people using a simple random sampling technique, a sample of 92 people was obtained which was calculated using the formula developed by Slovin with an error rate of 5%. Data collection techniques with questionnaires and documentation were then analyzed using Partial Least Square (PLS). The results of the study state that Job Satisfaction is in the very good category. While Job Insecurity, Work Engagement and Turnover Intention are in the good category. Job satisfaction has no significant effect on Work Engagement, Job Insecurity has a significant effect on Work Engagement, Job satisfaction and Work Engagement have a significant effect on Turnover Intention, Job Insecurity has no significant effect on Turnover Intention, Job satisfaction has no significant effect on Turnover Intention through Work Engagement. Job Insecurity has a significant effect on Turnover Intention through Work Engagement.